Outer Membrane Proteins form Specific Patterns in Antibiotic-Resistant Edwardsiella tarda - Peng, Bo; Wang, Chao; Li, Hui; Su, Yu-bin; Ye, Jin-zhou; Yang, Man-jun; Jiang, Ming; Peng, Xuan-xian (Frontiers in Microbiology, 2017)
Outer membrane proteins of Gram-negative bacteria play key roles in antibiotic resistance. However, it is unknown whether outer membrane proteins that respond to antibiotics behave in a specific manner. The present study specifically investigated the differentially expressed outer membrane proteins of an antibiotic-resistant bacterium, Edwardsiella tarda, a Gram-negative pathogen that has caused a huge economic loss in aquaculture and a spectrum of intestinal and extraintestinal diseases in humans. The comparison of a clinically isolated strain to the laboratory derived kanamycin-, tetracycline- or chloramphenicol-resistant strains identified their respective outer membrane proteins expression patterns, which are distinct to each other. Similarly, the same approach was utilized to profile the patterns in double antibiotic-resistant bacteria. Surprisingly, one pattern is always dominant over the other as to these three antibiotics; the pattern of chloramphenicol is over tetracycline, which is over kanamcin. This type of pattern was also confirmed in clinically relevant multidrug-resistant bacteria. In addition, the presence of plasmid encoding antibiotic-resistant genes also alters the outer membrane protein profile in a similar manner. Our results demonstrate that bacteria adapt the antibiotic stress through the regulation of outer membrane proteins expression. And more importantly, different outer membrane protein profiles were required to cope with different antibiotics. This type of specific pattern provides the rationale for the development of novel strategy to design outer membrane protein arrays to identify diverse multidrug resistance profiles as biomarkers of clinical medication.